Injuries and time loss in elite judo athletes: a Korean prospective cohort study - Kim, C. W.; Park, K. J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Few epidemiological studies have investigated pain and time loss due to sports injury. We analyzed the specific patterns of injury among Korean elite judo athletes and examined the effects of pain on time loss. We also assessed the association between the type of injury and time loss. METHODS: We prospectively collected data on elite judo athletes at the Korean Training Center for the year 2019. The athletes were assessed by sports medicine doctors, and data were stratified according to sex, weight class, and injury location. We used Chi2 tests to compare groups. Injury rates were expressed as Poisson rates with 95% confidence intervals. One-way analysis of variance was used to investigate the pain scores and time losses due to sports injury. RESULTS: The study included 232 athletes whose 606 injuries (annual average, 2.61 injuries/athlete) were recorded. Female athletes had higher injury rates than male athletes. Overall, most injuries occurred in the lower extremities (38.12%), followed by the upper extremities (36.80%), trunk (17.66%), and head and neck area (7.43%). Injury severity significantly differed according to the body regions in the weight classes. The pain score and time loss differed significantly according to the type of injury. When the pain score increased by 1, the time loss increased by approximately 1.47 days. CONCLUSIONS: Among all weight classes, female athletes had a higher injury rate than male athletes. The pain score and time loss varied depending on the type of injury, with pain score being associated with time loss.